Microscopic Behaviour of Hypersensitive Transition Observed in Some Er(III) Doped Systems - Verma, R.S.; Joshi, G.K. (Asian Journal of Chemistry, 2010)
The saturated organic ligand environment produced by various ligands in 50% ethanol, around Er(III) ion has been studied with respect to hypersensitive transition involved in the system. The spectroscopic data for the hypersensitive transition has been correlated with the thermodynamic behaviour of the said transition. Thermodynamic parameters include thermodynamic efficiency, work function and partition function of the said transition.